Protesting the lockdown: geo-indexing a movement publicly opposing Covid-19 policies on Facebook. - Mercea, Dan; Saker, Michael; Santos, Felipe G. (Social Movement Studies, 2024)
The Covid-19 pandemic saw restrictions being implemented to curb the spread of the virus. This seeded anti-lockdown demonstrations across the globe. Leveraging network, quantitative and qualitative textual analysis tools, we scrutinize the expression of opposition to these restrictions on 96 public Facebook groups and pages, and its connection to physical places across the globe. To grapple with this relation, we propose the concept of geo-indexing as the practice of adding meaning to physical places on social media and identify a transnational network of geo-indexed posts. Importantly, this geo-indexed opposition was framed as unified against an unjust and undemocratic imposition of restrictive measures. The language used in some of this communication was conspiratorial, albeit to a lesser degree than expected. Moreover, geo-indexed posts were used to evidence the scale of public mobilization, the cohesion of the protests, to articulate the virtue of transgressing health measures and to extoll those who said or did so, across multiple sites.